2019
DOI: 10.1007/s00464-019-06666-5
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional versus two-dimensional high-definition laparoscopy in cholecystectomy: a prospective randomized controlled study

Abstract: BackgroundWhile 3D laparoscopy increases surgical performance under laboratory conditions, it is unclear whether it improves outcomes in real clinical scenarios. The aim of this trial was to determine whether the 3D laparoscopy can enhance surgical efficacy in laparoscopic cholecystectomy (LCC).MethodThis prospective randomized controlled study was conducted between February 2015 and April 2017 in a day case unit of an academic teaching hospital. Patients scheduled for elective LCC were assessed for eligibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 13 publications
3
23
1
Order By: Relevance
“…Our findings, which could be expected to be widely applicable, are comparable with the original 1998 and very recent 2D/3D LC RCT reports although our notable absence of subjectively reported side effects and eye symptoms suggests contemporary 3D technology holds improved usability [24,26]. Our data suggests specialist LC performance was not altered by the technology used, possibly as the participating surgeon experience allowed them to overcome the loss of depth perception.…”
Section: Discussionsupporting
confidence: 87%
“…Our findings, which could be expected to be widely applicable, are comparable with the original 1998 and very recent 2D/3D LC RCT reports although our notable absence of subjectively reported side effects and eye symptoms suggests contemporary 3D technology holds improved usability [24,26]. Our data suggests specialist LC performance was not altered by the technology used, possibly as the participating surgeon experience allowed them to overcome the loss of depth perception.…”
Section: Discussionsupporting
confidence: 87%
“…16 Other studies 28,36,37 have shown technical improvement using 3-D laparoscopic systems, but the results have been inconsistent. A prospective, randomized clinical trial 16 The total number of error-related events was significantly lower when the 3-D system was used;…”
Section: Discussionmentioning
confidence: 99%
“…In laparoscopic cases, a substantial number of these events are associated with depth perception, as evidenced by a study that evaluated 252 cases of laparoscopic cholecystectomy, in which 97% of surgical accidents occurred as a result of visual misperceptions. [13][14][15][16] In the past 20 years, the advancement of laparoscopic technology has led to increased safety, better precision, and improved efficiency in the OR, but the lack of depth perception when using traditional 2-dimensional (2-D) laparoscopic systems remains a major limitation. 17 Three-dimensional laparoscopic systems provide direct stereoscopic depth, which may improve operative speed and technical performance in laparoscopic procedures.…”
Section: Introductionmentioning
confidence: 99%
“…However, these were smaller studies with less statistical power. Koppatz et al recently reported the largest 3D HD versus 2D HD laparoscopic cholecystectomy study to date, with over 100 participants in each arm [22]. They showed no difference in operative times or complication rates between 3D and 2D, including on subgroup analysis for surgical experience.…”
Section: Discussionmentioning
confidence: 99%